PERANCANGAN WEBSITE E-COMMERCE EXPRESS ORDER SYSTEM FOR RESELLER DROPSHIPPER MENGGUNAKAN HYPERTEXT PREPROCESSOR - Arrum Pramesti; Dony Novaliendry; Titi Sriwahyuni (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
Pramesti branded is an online store selling bags, clothes and cosmetics, where the sales system still manual and not computerized. Pramesti Branded resellers have had many both inside and outside the city of Bengkulu city. To solve the above problem, namely to increase sales, minimize the work and provide the needs of customers primarily acts as a reseller then Pramesti Branded want to use technology in the marketing and sales strategies by designing an e-commerce system for express orders dropshiper resellers. To build an application e-commrce express order system for resellers dropshiper analysis in the design of systems that are used to describe the system model using tools such as UML (Unified Modeling Language) in order to facilitate the transfer of the concept system designed to be a program in the form of a use case diagram, class diagram, activity diagram, deployment diagram, components of the diagram, statechart diagram, sequence diargram and in database design using mySQL database. Based on the case study it can be concluded that the application of e-commrce express order system for resellers dropshiper who made ​​this can be a media campaign that helped increase sales, especially for resellers and reduce operating costs for companies and consumers to facilitate the process of booking and payment of a product because it is done online. Keywords        : Reseller Dropshipper, Express Order System